30.7k views
4 votes
Simplify p(p - q) - q(q - p). p 2 - q 2 p 2 + q 2 p 2 + pq - q 2 p 2 - pq - q 2

2 Answers

2 votes
p^2 - pq - q^2 + pq
= p^2 - q^2
User Ignas
by
6.3k points
3 votes

Answer:

The solution of the expression is
p(p-q)-q(q-p)=p^2-q^2

Explanation:

Given : Expression
p(p-q)-q(q-p)

To find : Simplify the expression?

Solution :

Step 1 - Write the expression,


p(p-q)-q(q-p)

Step 2 - Apply distributive property,
a(b+c)=ab+ac


p(p-q)-q(q-p)=p^2-pq-q^2+qp

Step 3 - Add like terms,


p(p-q)-q(q-p)=p^2-q^2

Therefore, The solution of the expression is
p(p-q)-q(q-p)=p^2-q^2

User Bab
by
5.3k points